Spatial and temporal variability of sea surface height of bay of bengal derived from satellite altimetry - Peter, Benny Neettumkara (2012)
The spatial and temporal variability of sea surface height anomaly of Bay of Bengal is derived from satellite altimeter observations for the period of 1993-2008. The data used are the weekly Maps of Sea Level Anomaly with 1/3 x 1/3 longitude and latitude resolution weekly files. Annual average of sea level anomaly field is estimated to understand the long term variability. Empirical Orthogonal Functional analysis has been carried out to derive the spatial structure and temporal amplitude of the variability. The first three modes of EOFs capture 80% of the total variance. The temporal amplitude clearly exhibits the influence of climate modes on the sea level of Bay of Bengal.